Assessment in situ of genotoxicity in tadpoles and adults of frog Hypsiboas cordobae (Barrio 1965) inhabiting aquatic ecosystems associated to fluorite mine - Pollo, Favio Ezequiel (2016)
Non-lethal biological techniques such as blood biomarkers have gained attention due to their value as early signals of anthropic effects of contamination representing significant tools to evaluate ecosystems health. We evaluate and characterize in situ genotoxicity of water samples collected from aquatic ecosystems around a fluorite mine using amphibian frogs Hypsiboas cordobae as bioindicator species complemented with 16 physicochemical parameters. Four stations associated with fluorite mine sampling were sampled: a stream running on granitic rock with natural high fluorite content; two streams both running on metamorphic rock with low fluorite content; and an artificial decantation pond containing sediments produced by fluorite flotation process with high variation in physicochemical parameters. We analyses the blood of tadpoles and adults of H. Cordobae, calculated frequencies of micronuclei, erythrocyte nuclear abnormalities, mitosis, immature and enucleated erythrocytes. Individuals were measured and weighed and body condition was calculated. The results of this study indicate that individuals of decantation pond are exposed to compounds or mixtures which are causing cell damage when compared to those that were collected of stream. Larval stage was more vulnerable than the adult phase and it could be related mainly to the higher exposure time to xenobiotics, which can penetrate easily by skin, mouth and gills; additionally this site offers a reduced availability of food than other sites. Therefore, chronic exposure to pollutants could derive in degenerative and neoplastic diseases in target organs. Moreover these individuals may experience reproductive and behavioral disturbances which could lead to population decline in the long term.